Kajian Yuridis Pertanggungjawaban Hukum dalam Tindak Pidana Penadahan - Samsuto Samsuto; Yasmirah Mandasari Saragih; Biner Sihotang (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study analyzes the construction of criminal liability in the crime of handling stolen goods, focusing on situations where the perpetrator purchases or receives goods without knowing they are the result of a crime, especially when the economic value is relatively small, i.e., below Rp5,000,000. This normative study uses a legislative approach by examining Article 591 of Law Number 1 of 2023 on the Criminal Code (KUHP), as well as a conceptual approach to the theory of fault (schuld) and the principle of proportionality. The study's findings show that in transactions involving low-value goods, proving the subjective element of "knowing or should have known" becomes highly problematic because the element of intent (dolus) is often not met without objective suspicious indications. The concept of price fairness plays a key role as the primary indicator of normal transactions and weakens the assumption that the perpetrator should suspect the illegal origin of the goods. This study recommends that law enforcement consider using non-criminal mechanisms, such as restitution or mediation, to achieve substantive justice and avoid excessive criminalization.